Multimodal Representation of Gender in Two Senior High School Textbooks - Asriyama, Weksa Fradita; Saleh, Mursid; Wuli Fitriati, Sri (English Education Journal, 2020)
The urgency in revealing multimodal gender representation in education is the background of this study. Two English textbooks for Senior High School students entitled Ã¢â‚¬Å“Talk ActiveÃ¢â‚¬Â and Ã¢â‚¬Å“Pathway to EnglishÃ¢â‚¬Â were used as the subjects of the study. The objectives of the study are to explain multimodal representation of gender through its typical roles, conversational roles, and semantic representation found in the aforementioned English textbooks. In gathering the data, Brugeilles and CromerÃ¢â‚¬â„¢s (2009) gender representation analysis was adapted as instruments to gain the data for gender typical roles, Francis and HunstonÃ¢â‚¬â„¢s (2002) analysis was employed to get the data for gender conversational roles, and lastly, MillsÃ¢â‚¬â„¢ (1995) feminism language was used to collect the data for gender semantic representation. The findings revealed that in both textbooks males have typical roles as breadwinners in dometic sphere and leaders in social and occupational spheres, whereas females have nurturing roles in domestic phere, followers roles in social sphere and subordinates in occupational spheres. With regard to gender conversational roles, the findings shown that in Ã¢â‚¬Å“Talk ActiveÃ¢â‚¬Â males are the dominant speakers and females are the deferential speakers, while in Ã¢â‚¬Å“Pathway to EnglishÃ¢â‚¬Â, the opposite happened. Lastly, the finding of gender semantic representation analysis told that both textbooks represent both gender equally, although some sexist Ã¢â‚¬ËœmanÃ¢â‚¬â„¢ affixes were found.